Pengaturan Penguasaan Tanah Bekas Hak Guna Usaha Dalam Pembaharuan Agraria - I Gusti Agung Ngurah Klaustra Adhipermana; Ketut Kasta Arya Wijaya; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
Land plays a very useful role for living things, so there must be national assistance to control and manage land well, evenly, and for the public interest. The question of this research is how the management of land use rights can be regulated in land reform and what are the legal implications of managing land use rights by the community. This type of investigation uses a normative legal investigation. The types and income of the data are carried out with two primary and secondary component data. The process of obtaining data employs investigations and the preparation of reviews related to the legal issues being investigated. The juridical data analysis process applied is descriptive analysis. Sources of an investigation indicate that the previous land ownership arrangements were in line with Article five of Presidential Decree No. 32, 1979. After fulfilling the requirements and relating to the interests of the people, the people are prioritized. The legal consequence of the previous owner of land rights and the law on land ownership is that if they do not extend the term of land ownership, the land itself becomes national land.